2008
DOI: 10.2298/bah0802087g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the probiotic 'Lactina' on some biological parameters and nonspecific resistance in neonatal pigs

Abstract: Twenty four pregnant Danube white sows were allocated to 4 groups. All animals were fed basal diet formulated to meet their nutrient requirements. In addition to the basal diet, the sows from the II group were given the probiotic "Lactina" (500 g/ton) from the 5 day of pregnancy until the weaning of their offspring (35 days of age ) and their piglets were offered 800 g/ton Lactina during the pre-starter period and 500 g/ton throughout the starter period. The probiotic was only supplemented to the sows in the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
5
6
0
Order By: Relevance
“…The obtained results confined the previous research as Subrata et al,1997 and Abdel -Azeem, 2002. Who found that yeast supplementation had no adverse effects on blood componants or liver function. Our observations corroborated data published by some authors (Panda et al, 2000;Kannan et al, 2005;Gudev et al, 2008 andParyad andMahmoudi, 2008) who stated that there was a decrease in plasma cholesterol for chicks fed diets contain dry yeast. Values (Mean± SE) with different superscripts in a row differ significantly (P<0.05); T 1 =Control; T 2 = 0.50% Yeast (Saccharomyces Cerevisiae) powder; T 3 =0.50% Aloe vera (Aloe barbadensis) powder; T 4 =0.50% Yeast + 0.50% Aloe vera powder in basal diet.…”
Section: Resultssupporting
confidence: 93%
“…The obtained results confined the previous research as Subrata et al,1997 and Abdel -Azeem, 2002. Who found that yeast supplementation had no adverse effects on blood componants or liver function. Our observations corroborated data published by some authors (Panda et al, 2000;Kannan et al, 2005;Gudev et al, 2008 andParyad andMahmoudi, 2008) who stated that there was a decrease in plasma cholesterol for chicks fed diets contain dry yeast. Values (Mean± SE) with different superscripts in a row differ significantly (P<0.05); T 1 =Control; T 2 = 0.50% Yeast (Saccharomyces Cerevisiae) powder; T 3 =0.50% Aloe vera (Aloe barbadensis) powder; T 4 =0.50% Yeast + 0.50% Aloe vera powder in basal diet.…”
Section: Resultssupporting
confidence: 93%
“…Reduction in circulating levels of cholesterol and LDL with supplemental yeast was reported by other researchers [8,9] who stated that probiotics could contribute to the regulation of serum cholesterol concentrations by deconjugating bile salts.…”
Section: Introductionmentioning
confidence: 55%
“…The results showed that administration of L. johnsonii XS4 in diets towards the end of pregnancy and during lactation had positive effects on the performance of sows, increasing litter weight at birth, 20-day litter weight, the number of piglets at weaning and weaning litter weight, along with a significant increase in serum IgG levels and a decrease in alanine aminotransferase concentrations [ 31 ]. Lactina, a mixture of Streptococcus thermophiles , E. faecium , L. bulgaricus , L. acidophilus , L. helveticus and L. plantarum , supplemented both to sow and piglet diets, increased complement activity in piglets at 5 days of age compared with a control group, while the addition of Lactina to sows only or to piglets only did not produce any significant effects [ 32 ]. Another probiotic mixture of B. licheniformis and B. subtilis (normal feed plus the probiotic mixture vs. untreated control group) was shown to improve sow feed intake and decrease sow weight loss during the sucking period [ 8 ].…”
Section: Applications Of Lactic Acid Bacteria In Pigsmentioning
confidence: 99%